Effects of Shampoo Containing Plantago asiatica L. on Hair Thickness, Density, and Shedding: A Double-Blind, Randomized, Placebo-Controlled Clinical Study - Jiyeon Lee; Ah-Reum Jung; Jun-Hwan Jang; Jun-Tae Bae; Wanil Kim (Cosmetics)
This double-blind, randomized, placebo-controlled clinical study evaluated the efficacy of a shampoo containing Plantago asiatica L. on hair health in adults aged 20–60. Following a 4-week wash-out period, participants used either the test shampoo or a placebo for 12 weeks. Hair measurements using phototrichograms and hair count tests were conducted at baseline and at weeks 4, 8, and 12. The test group demonstrated progressive improvements in hair strand thickness (0.009 mm, 0.017 mm, and 0.020 mm at weeks 4, 8, and 12, respectively) and hair density (0.9 hairs/cm2 at weeks 4 and 8, 1.1 hairs/cm2 at week 12). Additionally, a significant reduction in hair shedding was observed compared to the placebo group. These findings suggest that shampoo containing Plantago asiatica L. effectively improves hair thickness and density while reducing hair loss, offering a natural solution for hair care concerns.